Chemistries and applications of DNA-natural product conjugate - Chen, Yuanyuan; Li, Wenting; Xing, Hang (Frontiers in Chemistry, 2022)
Natural products and their derivatives have made great contributions to chemotherapy, especially for the treatment of tumors and infections. Despite the achievements, natural product-based small molecule drugs usually suffer from side effects, short circulation time, and solubility issue. To overcome these drawbacks, a common approach is to integrate another bio-functional motif into a natural product compound, enabling targeted or synergistic therapy. One of the most promising strategies is to form a DNA-natural product conjugate to improve therapeutic purposes. The incorporated DNA molecules can serve as an aptamer, a nucleic-acid-based congener of antibody, to specifically bind to the disease target of interest, or function as a gene therapy agent, such as immuno-adjuvant or antisense, to enable synergistic chemo-gene therapy. DNA-natural product conjugate can also be incorporated into other DNA nanostructures to improve the administration and delivery of drugs. This minireview aims to provide the chemistry community with a brief overview on this emerging topic of DNA-natural product conjugates for advanced therapeutics. The basic concepts to use the conjugation, the commonly used robust conjugation chemistries, as well as applications in targeted therapy and synergistic therapy of using DNA-natural product conjugates, are highlighted in this minireview. Future perspectives and challenges of this field are also discussed in the discussion and perspective section.